The Exchange Rate in a Dynamic-Optimizing Current Account Model with Nominal Rigidities : A Quantitative Investigation - Kollman, Robert (IMF Working Papers; Working Paper ;, 1997)
This paper studies dynamic-optimizing model of a semi-small open economy with sticky nominal prices and wages. The model exhibits exchange rate overshooting in response to money supply shocks. The predicted variability of nominal and real exchange rates is roughly consistent with that of G-7 effective exchange rates during the post-Bretton Woods era. The model predicts that a positive domestic money supply shock lowers the domestic nominal interest rate, that it raises output and that it leads to a nominal and real depreciation of the country's currency. Increases in domestic labor productivity and in the world interest rate too are predicted to induce a nominal and real exchange rate depreciation.